Physical performance and motivation to exercise - Stankiewicz, Błażej; Stankiewicz, Jacek; Mandzák, Peter; Kotyśko, Martyna (Journal of Education, Health and Sport, 2017)
The study is an attempt to assess the impact of self-evaluation and motivation on physical exercise. In the chapter, material and methods describe the specificity of the research methodology, their purpose being to compare the outcome of subjective evaluation after FMS with the objective outcome of FMS, self-esteem, and motivation analysis for sport, and the hypothesis that Additional activity does not affect the higher self-esteem and it can be assumed that the age range does not affect the result of external motivation. Materials and research tools such as questionnaire, FMS test and SMS scale were also defined. The research was done on a group of 30 people. The group included 14 women and 16 men. More than half of the respondents (53%) are between 20 and 22 years of age, 27% are between 23 and 24 years old, and 20% are between 17 and 19 years of age. Analysis of the research revealed that as many as 19 people trained their discipline over 6 years, another 9 had a training period of 2-4 years, while only 2 respondents are beginners. It has also been reported that men in the research group practice up to 7 training units a week more than women. Up to half of the group, 15 people practice their amateur discipline without achieving any sports successes, 9 people are players and 2 and 3 league players, while only 6 are participating in the championship. In turn, 24 out of 30 respondents have additional physical activity. Participants in the study rated their physical fitness very high, 28 out of 30 rated it very good and good, and only 2 rated it sufficiently. The most subjectively assessed element of physical fitness was the strength that 22 people rated very good and good. This can be a testimony to the volleyballs grown by the test subjects - 43%; Other sports 27% (tennis, table tennis, hammering, rowing, basketball, football); Bodybuilding 17% and combat sports 13%. The lowest rated motor ability is flexibility, 20 respondents rated either sufficiently or badly. This can be a sign of neglect of training in terms of exercise flexibility, as evidenced by the numerous traumas reported by the persons examined. After summing up the results of subjective assessments of the seven FMS tests, the following result was obtained: Half of the subjects surveyed ranged from 10 to 13 points, another 13 assessed their trials in the range of 15-20, while the other two showed low self-esteem. Go for 9 and 4 points. Of the 30 people tested, only 6 of them do not take any additional physical activity. In this group, only one subjective observation can be observed after the tests have been performed. The results of 5 other people are comparable to the results of people who practice additional sports. This fact makes it possible to make a claim and to confirm the hypothesis that additional physical activity does not affect self-esteem. SMS Scale (Sport Motivation Scale) study. "SMS" gives you the opportunity to explore the level of motivation in relation to physical activity, such as internal motivation, the results of which are as follows: 13 respondents rated their internal motivation high, another 13 were sufficient, and 4 were poorly rated. Range from 6 to 10 points. Research has shown that internal motivation in the research group is very high, 26 in 30 subjects are motivated by internal motivation to exercise. Thanks to the "SMS" scale, external motivation was also assessed. Research has shown that 26 respondents questioned the impact of external factors on motivation for physical activity. For 3 people, external motivation is important and 1 person has confirmed that external factors have a significant impact on her personal motivation. After comparing these two analyzes, it can be stated that there are no external factors, but internal factors are the main motivator when it comes to practicing sport. The "FMS" study (functional movement screen) showed that the majority of the respondents had a good self-assessment. The differences between the subjective assessment and the objective evaluation of these individuals were a maximum of 4 points. In the next 6 cases, the inadequate self-esteem may be observed, as the subjects are assessed too low for the FMS test. Differences between subjective and objective ratings ranged from 5 to a maximum of 8 points. In one case, an inadequate self-assessment was observed, where the test result was lower than the one declared.